Maternal 5mCpG Imprints at the PARD6G-AS1 and GCSAML Differentially Methylated Regions Are Decoupled From Parent-of-Origin Expression Effects in Multiple Human Tissues - de Sá Machado Araújo, Graziela; da Silva Francisco Junior, Ronaldo; dos Santos Ferreira, Cristina; Mozer Rodrigues, Pedro Thyago; Terra Machado, Douglas; Louvain de Souza, Thais; Teixeira de Souza, Jozimara; Figueiredo Osorio da Silva, Cleiton; Alves da Silva, Antônio Francisco; Andrade, Claudia Caixeta Franco; da Silva, Alan Tardin; Ramos, Victor; et al. (Frontiers in Genetics, 2018)
A hallmark of imprinted genes in mammals is the occurrence of parent-of-origin-dependent asymmetry of DNA cytosine methylation (5mC) of alleles at CpG islands (CGIs) in their promoter regions. The 5mCpG asymmetry between the parental alleles creates allele-specific imprinted differentially methylated regions (iDMRs). iDMRs often are coupled to the transcriptional repression of the methylated allele and the activation of the unmethylated allele in a tissue-specific, developmental-stage-specific and/or isoform-specific fashion. iDMRs function as regulatory platforms, built through the recruitment of chemical modifications on histones to achieve differential, parent-of-origin-dependent chromatin segmentation states. Here, we used a comparative computational data mining approach to identify 125 novel constitutive candidate iDMRs that integrate the maximal number of allele-specific methylation region records overlapping CGIs in human methylomes. Twenty-nine new candidate iDMRs display gametic 5mCpG asymmetry, and another 96 are candidate secondary iDMRs. We established the maternal origin of the 5mCpG imprints of one gametic (PARD6G-AS1) and one secondary (GCSAML) iDMRs. We also found a constitutive hemimethylated, nonimprinted domain at the PWWP2AP1 promotor CGI with oocyte-derived methylation asymmetry. Given that the 5mCpG level at the iDMRs is not a sufficient criterion to predict active or silent locus states and that iDMRs can regulate genes over a distance of 1-Mb, we assessed the allele transcriptional expression profiles in SNPs across 4.6-Mb spans around the novel maternal iDMRs in RNA-Seq experiments from the Genotype-Tissue Expression project and public archives. We showed that PARD6G-AS1 and GCSAML are expressed biallelically in multiple tissues. We found evidence of tissue-specific monoallelic expression of ZNF124 and OR2L13, located 363-kb upstream and 419-kb downstream, respectively, of the GCSAML iDMR. We hypothesize that the GCSAML iDMR regulates the tissue-specific, monoallelic expression of ZNF124 but not of OR2L13. We also annotated the non-coding epigenomic marks in the two maternal iDMRs using data from the Roadmap Epigenomics project and showed that the PARD6G-AS1 and GCSAML iDMRs achieve contrasting activation and repression chromatin segmentations. Lastly, we found that the maternal 5mCpG imprints are perturbed in several hematopoietic cancers. We conclude that the maternal 5mCpG imprints at PARD6G-AS1 and GCSAML iDMRs are decoupled from parent-of-origin transcriptional expression effects in multiple tissues.